Influence of polyols on the skin of experimental animals - L. V. Anischenko; V. L. Mykhaylenko; R. A. Fedorchenko; N. S. Badiuk (Kazimierz Wielki University, 2017)
In the article the results of experimental studies aimed at identifying of sensitizing and allergenic properties of polyols oral intake of warm-blooded animals. The task of the research stage to assess skin-resorptive action alternative was to obtain answers about the possibility substances penetrate intact skin and cause intoxication of the organism in multiple steps. Found that polyols do not have the skin-resorptive properties. Skin-resorptive effect inherent in all substances lesser degree. Visible symptoms of intoxication in the clinical picture when assessing the penetration of substances through the skin is not detected.